Regulatory T Cells and Plasmacytoid Dendritic Cells Within the Tumor Microenvironment in Gastric Cancer Are Correlated With Gastric Microbiota Dysbiosis: A Preliminary Study - Ling, Zongxin; Shao, Li; Liu, Xia; Cheng, Yiwen; Yan, Chongxian; Mei, Ying; Ji, Feng; Liu, Xiaosun (Frontiers in Immunology, 2019)
Substantial evidence indicates that gastric microbiota dysbiosis, immune system dysfunction especially immune escape are critical for gastric cancer (GC) occurrence and progression. As two important elements of tumor microenvironment (TME), the relationship between gastric microbiota and tumor-immune microenvironment is still unclear. Our present study aimed to explore the correlation between gastric mucosal microbiota in different microhabitats and its corresponding gastric immunosuppressive cells such as regulatory T cells (Tregs) and plasmacytoid dendritic cells (pDCs) in the TME. A cohort of 64 GC patients without preoperative chemotherapy was enrolled retrospectively, and 60 normal, 61 peritumoral and 59 tumoral tissues were obtained for gastric mucosal microbiota analysis and immunohistochemistry analysis. From different microhabitats, BDCA2+pDCs and Foxp3+Tregs were observed positively correlated, and increased in tumoral and peritumoral tissues compared to normal ones. The diversity, composition and function of gastric mucosal microbiota also changed more significantly in tumoral tissues than those in normal and peritumoral ones. With pearson’s correlation analysis, we found that several non-abundant genera such as Stenotrophomonas and Selenomonas were positively correlated with BDCA2+pDCs and Foxp3+Tregs respectively, while Comamonas and Gaiella were negatively correlated with BDCA2+pDCs and Foxp3+ Tregs respectively. The increased BDCA2+pDCs and Foxp3+Tregs might be modulated by gastric mucosal microbiota, both participated in the immunosuppression microenvironment of GC, which might provide evidence to establish new strategies in antitumor therapy targeting on gastric microbiota.